A simple chart to identify non-familial short stature. Issue 2 (1st February 2000) - Cole, T J
Abstract : OBJECTIVE: To develop a chart to identify non-familial short stature. DESIGN: A height chart that adjusts for maternal, paternal, midparental, or sibling height based on the British 1990 height reference. MAIN OUTCOME MEASURE: Height between 2 and 9 years of age. RESULTS: The chart identifies children whose height is below the familially adjusted 0.4th centile, assuming a correlation of 0.4 between child height standard deviation score (SDS) and familial height SDS. The adjustment can be for parents, either alone or together, or for a sibling aged 2–9 years. The chart identifies about 2 children/1000 over and above the 4/1000 identified by the unconditional 0.4th centile. CONCLUSION: The chart should be a useful addition to screening programmes for short stature.